Signless Laplacian Spectral Conditions for Hamiltonicity of Graphs - Guidong Yu; Miaolin Ye; Gaixiang Cai; Jinde Cao (Journal of Applied Mathematics)
We establish some signless Laplacian spectral radius conditions for a graph to be Hamiltonian or traceable or Hamilton-connected.